1970
DOI: 10.4314/njp.v42i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ perception of the use of banked human milk for feeding of the infants

Abstract: Background: Human breast milk is the most healthful form of milk for human babies. Every infant deserves the best possible start in life in terms of nutrition by breastfeeding or receiving donated human milk. Breast milk is very important for the infant’s growth and well-being that the non-availability of the mother should not deprive the infant from its benefits. To enhance the availability and use of human breast milk for hospitalized babies whose mothers may not have enough milk, there is the need to embark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Most units started enteral feeding with trophic feeds ranging between 10 and 20 ml/kg/day, with daily advancements of 10–20 ml/kg/day, though there is evidence from developed countries that faster advancement of 30–40 ml/kg/day may be safe and facilitates earlier attainment of full enteral feeds ( 8 , 27 ) few of the units in this survey advanced more than 20 ml/kg/day. The WHO feeding guidelines for preterm infants recommend a daily increase “up to” 30 ml/kg for LMICs ( 14 ) and this may be the reason for the observed practice. The fact that the clinical status of the infants in sSA and the level of monitoring and nursing care might not be similar to those in high income countries, coupled with the suboptimal nutritional, economic and overall conditions of mothers as well as the health system set up ( 28 ) may all intricately interact to interfere with lactation, milk expression and storage and feeding regimens in these units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most units started enteral feeding with trophic feeds ranging between 10 and 20 ml/kg/day, with daily advancements of 10–20 ml/kg/day, though there is evidence from developed countries that faster advancement of 30–40 ml/kg/day may be safe and facilitates earlier attainment of full enteral feeds ( 8 , 27 ) few of the units in this survey advanced more than 20 ml/kg/day. The WHO feeding guidelines for preterm infants recommend a daily increase “up to” 30 ml/kg for LMICs ( 14 ) and this may be the reason for the observed practice. The fact that the clinical status of the infants in sSA and the level of monitoring and nursing care might not be similar to those in high income countries, coupled with the suboptimal nutritional, economic and overall conditions of mothers as well as the health system set up ( 28 ) may all intricately interact to interfere with lactation, milk expression and storage and feeding regimens in these units.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of recommended strategies is fraught with challenges in the context of resource limitations, a common problem in sSA. Early initiation of enteral feeds and exclusive feeding with breastmilk and fortification of human milk for hospitalized very preterm/VLBW babies is common in high income countries due to the availability of breastmilk banks and fortifiers, which are not available in most centers in sSA ( 14 ). In addition, early parenteral nutrition used in HICs, to provide the necessary nutrients whilst full enteral feeds are established, is not widely available and affordable in most of sSA.…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the 25.8% reported in South-south Nigeria but lower than the 39% reported in south-east Nigeria. 12,18 The suboptimal knowledge is not likely related to maternal education as the majority of participants had post-secondary school education. The lack of HMB practice in Nigeria and neighbouring countries may contribute to the low awareness.…”
Section: Discussionmentioning
confidence: 96%
“…Less than 50% of participants in this study received information about HMB from healthcare workers, similar to what was reported in a study in Benin. 18 Participants in the study expressed unwillingness to donate breastmilk due to concerns about transmission of diseases or infections and feeling that it was not the right thing to do. This is consistent with similar reports from other countries, such as Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…This is much lower than what has been reported in studies amongst mothers in Turkey, China but similar to what has been reported in some parts of Nigeria. 13,[15][16][17] . The difference in awareness level between mothers in our environment and those cited maybe partly due to less availability and accessibility of electronic media for dissemination of relevant health investigation compared to these countries.…”
Section: Discussionmentioning
confidence: 99%